Insulin resistance and -cell function in Colombian mestizo and Embera-Chamí populations and their relation with adiposity degree (2017)
Background and objective: Insulin resistance (IR) is a condition favored by metabolic and endocrine changes experienced by adipose tissue in the context of obesity. The prevalence and the presentation of both IR and obesity vary among the populations, and may be affected by ancestral genetic composition among other factors. The aim of this study was to compare the presence of IR and obesity in Amerindians of the Embera-Chamí ethnicity and Colombian mestizo population. Patients and methods: A sample of 630 individuals, 471 mestizos and 159 Amerindians of the Embera-Chamí ethnicity, from the general population of Colombia were studied. For each participant, anthropometric and biochemical measurements, as well as blood pressure and the Homeostatic Model Assessment (HOMA) of IR and -cell function (%B) were recorded. These values were compared between the two populations. Results: While prevalence of central obesity was similar in both populations (48.7% and 42.6% in the mestizo and Embera groups respectively; p = 0.148), body mass index (BMI) values suggested a higher prevalence of overweight in the Embera than in mestizo population (43.4% Embera, 31.8% mestizo; p = 0.027). Despite the similarities in the prevalence of HOMA-IR and HOMA-%B status between both populations, the Embera population had a significantly greater pancreatic ˇ-cell function, higher insulin levels, and better glucose control, across BMI and central obesity categories, than the mestizo population. Conclusion: There are differences in aspects related to energy metabolism between the samples of the mestizo and Amerindian populations analyzed